1994
DOI: 10.4037/ajcc1994.3.6.452
|View full text |Cite
|
Sign up to set email alerts
|

Use of extracorporeal photochemotherapy in heart transplant recipients during acute rejection: a case study

Abstract: Despite the growing availability of improved immunosuppressive agents, acute and chronic rejection episodes remain a major complication in heart transplant recipients. The rejection of allografts is a normal part of the body's response to foreign antigens. The key to controlling this response is to administer a regimen of multiple immunosuppressive drugs. Evidence indicates that by adding extracorporeal photochemotherapy to a standard immunomodulatory regimen, the rejection process can be reversed without sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…18 Multiple reports have been published demonstrating the efficacy of ECP for the treatment or prophylaxis of heart transplant rejection. [2][3][4][5][6][7][8][9][10][19][20][21] Rose and colleagues 7 reported the successful use of ECP as adjuvant immunotherapy in 4 heart transplant recipients with elevated levels of panel-reactive antibodies. Meiser and associates 6 demonstrated that ECP as adjuvant immunotherapy for heart transplant recipients significantly decreased the number of acute rejection episodes without increasing the number of infectious complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Multiple reports have been published demonstrating the efficacy of ECP for the treatment or prophylaxis of heart transplant rejection. [2][3][4][5][6][7][8][9][10][19][20][21] Rose and colleagues 7 reported the successful use of ECP as adjuvant immunotherapy in 4 heart transplant recipients with elevated levels of panel-reactive antibodies. Meiser and associates 6 demonstrated that ECP as adjuvant immunotherapy for heart transplant recipients significantly decreased the number of acute rejection episodes without increasing the number of infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports detailing the efficacy of ECP for the treatment and prevention of acute allograft rejection. [2][3][4][5][6][7][8][9][10] Taken together, these reports suggest that ECP is a safe, effective therapy with only minimal side effects.…”
mentioning
confidence: 95%